Pengaruh Norma Subyektif, Kinerja Aparatur, Kejelasan Sasaran Anggaran, Prosocial Behavior Terhadap Transparansi Dan Akuntabilitas - Wadi, Ikhwan; Furkan, Lalu M.; Rifa’i, Ahmad (E-Jurnal Akuntansi, 2020)
This study aims to empirically analyze the influence of   subjective norms, the performance of government officials, clarity of budget targets, and prosocial behavior on village financial transparency, the influence of subjective norms, performance of government officials, clarity of budget targets, prosocial behavior, and transparency on village financial accountability. The data source in this study uses primary data by distributing questionnaires to 20 villages in East Lombok Regency. The results of this study indicate that hypotheses (H1), (H2), and (H3) variables of subjective norms, performance of government officials, clarity of budget targets have a positive and significant effect on village financial transparency. Hypothesis (H4) prosocial behavior has a negative and significant effect on village financial transparency. Hypotheses (H5), (H6), and (H7), subjective norms, performance of government apparatus, and clarity of budget targets, have no effect and are significant to village financial accountability. prosocial behavior has a positive and significant effect on village financial accountability. Transparency has a negative and significant effect on village financial accountability . Keywords: Subjective Norms, Performance of Government Apparatus, Budget Target Clarity, Prosocial Behavior, Transparency, Accountability